A epistolografia das irmãs Lispector : nos intermúndios literários de Clarice - Silva, Luciana Aparecida (2016)
This work is a study of the scenes of the creation s Clarice Lispector process when she used the textual genre letter, based on the correspondence between the author and her sisters Tania Kaufmann and Elisa Lispector along the years of 1944 and 1959 - a period in which she lived in several countries following her diplomat husband . During her stay in a foreign territory, Clarice wrote a lot of letters, which were published in books called Correspondências (2002) and Minhas Queridas (2007), these books constitute a rich studying material about relationship of life and fiction. The emphasis of this research is in the letters considered as witness of the various stages of creation, because this genre is a specific form of writing about herself, talking about writers, and about everyday literary and artistic matters. Despite correspondences being a rich source for analyzing the literary work of the most acclaimed writers of our literature, epistolography has not yet reached the status it deserves and is often on the margins of research sources considered privileged by scholars and critics. The letters written by Clarice reveal a person tormented by literature itself and the enhancement and recognition of their creative process, in addition to launching new perspectives for the understanding of autobiographical traits that are often present in her fiction writing. The letters written by Clarice reveal a tormented person by literature itself and the enhancement and recognition of her creative process, in addition to it, her literary works open new perspectives for the understanding of autobiographical traits that are often present in her fiction writing. The study of life and work by epistolography side enabled us to understand more comprehensively his personal and artistic trajectory, as the author explains their fears, doubts and anxieties to their correspondents. The study of the life and work of Clarice enabled us to understand more her personal and artistic career, because the author exposes her fears, doubts and anxieties to her addressees. The fact that transformed her life in aesthetic experimentations performing made her important interlocutors as characters prepared to meet with themselves as human beings and as professionals.